Multi-band magnetotransport in exfoliated thin films of Cu x Bi2Se3 - Alexander-Webber, J. A.; Huang, J.; Beilsten-Edmands, J; Čermák, Patrik; Drašar, Čestmír; Nicholas, R.J.; Coldea, A.I. (My University, 2018)
We report magnetotransport studies in thin (<100 nm) exfoliated films of Cu x Bi2Se3 and we detect an unusual electronic transition at low temperatures. Bulk crystals show weak superconductivity with K and a possible electronic phase transition around 200 K. Following exfoliation, superconductivity is supressed and a strongly temperature dependent multi-band conductivity is observed for T < 30 K. This transition between competing conducting channels may be enhanced due to the presence of electronic ordering, and could be affected by the presence of an effective internal stress due to Cu intercalation. By fitting to the weak antilocalisation conductivity correction at low magnetic fields we confirm that the low temperature regime maintains a quantum phase coherence length nm indicating the presence of topologically protected surface states.
Více-pásový magnetotransport v exfoliovaných tenkých vrstvách CuxBi2Se3
Keywords: topological insulator; multi-band transport; magnetotransport; CuxBi2Se3; weak localisation; topologický izolátor; více-pásový transport; magnetotransport; CuxBi2Se3